KAJI EKSPERIMENTAL HIDROFOBISITAS DAUN DENGAN VARIASI VOLUME DAN BAHAN DROPLET - Rachmat Subagyo; Dedi Muliadi (Mechanical Engineering Department, Faculty of Engineering, Universitas Lambung Mangkurat, 2017)
Based on the measurement of droplet contact angle on the surface of taro leaf, droplet measurement using mineral water volume 1-5 ml respectively that is 159,325°, 154,628°, 152,430°, 151,833°, 150,199°, while in sea water that is 154,011°, 152,266°, 149,265°, 149,290°, 144,345°, and on cooking oil that is 35,407°, 40,206°, 42,825°, 46,997°, 49,807°. Based on the measurement of droplet contact angle on the surface of serai leaf, droplet measurement using mineral water volume 1-5 ml respectively that is 132,791°, 130,539°, 126,367°, 124,409°, 122,005°, while at sea water that is 126,319°, 121,409° , 118,856°, 109,273°, 106,950° and on cooking oil that is 34,683°, 36,760°, 39,739°, 43,603°, 52,837°. Based on the measurement of droplet contact angle on papaya leaf surface, droplet measurements using mineral water are 87,766°, 83,538°, 82,248°, 74,157°, 71,079°, while in sea water 84,523°, 83,059°, 80,017° , 71,346°, 70,167°, and on cooking oil are 34,367°, 38,086°, 40,597°, 43,933°, 47,339°. With the difference in fluid in each leaf, it can be seen the nature of the leaf, different leaves and different fluids in droplet droplets become related to the surface causing a decrease in contact angle.